Pengembangan Aplikasi Sistem Informasi Untuk Bisnis Pariwisata Indonesia - Amin, Bintang Arkaan; Hidayat, Syarif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Indonesia's economic progress is heavily influenced by the development of tourism, which has become a major source of income for the region and the nation at large. However, the current COVID-19 pandemic is changing the way global tourism works with reduced interest and number of tourists visiting various destinations. For this reason, a smart tourism approach is suggested as a viable solution to encourage a more interactive and captivating tourism experience. This research presents an app called Quexp app that presents missions and challenges during the tourism experience for users to complete. By rewarding users for their achievements, Quexp is envisioned as an innovative way to market and develop tourism destinations in a fun way that actively engages the community. This study examines the concept of smart tourism and the use of the Quexp app as a means to encourage travelers' curiosity and desire to see various tourism sites, thus contributing to understanding the development of sustainable adaptive tourism in the context of global change.